Pengaruh Komitmen Organisasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Penanaman Modal, Pelayanan Terpadu Satu Pintu, Tenaga Kerja Dan Transmigrasi Kabupaten Soppeng - Ahmad, Nabila; Jayadi Jayadi, Muhsin Wahid , (Pascasarjana STIE Amkop Makassar, 2025)
The purpose of this study is to examine the influence of organizational commitment and work discipline on employee performance at the Office of Investment, Integrated One-Stop Services, Manpower, and Transmigration of Soppeng Regency. The study was conducted over a one-month period, from December 2024 to January 2025. The population in this research consists of all civil. Servants. The sampling method used is the saturated sampling technique, where the entire population was used as the sample, resulting in a total of 42 respondents. This research utilized primary data obtained through direct field observation by distributing questionnaires/statements to the 42 respondents. The data analysis method used was multiple linear regression analysis. The results of the study indicate that: Partially, the organizational commitment variable has a negative and insignificant effect on employee performance, while work discipline has a positive and significant effect on employee performance. Simultaneously, organizational commitment and work discipline together have a significant influence on employee performance. Keywords: Organizational Commitment, Work Discipline, Employee Performance